2009
DOI: 10.1017/s1041610209008576
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of age-related memory deficits by differential outcomes

Abstract: These findings demonstrate, for the first time, that DOP can help elderly people overcome their memory limitations, and they draw attention to the potential of this procedure as a therapeutic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
7
22
0
6
Order By: Relevance
“…To our knowledge, this is the first time that such an effect has been reported in 7-year-old children. Some recent studies have shown that the DOP is effective in improving memory-based performance after short delays in normal aging, in young people, and in patients with alcohol-related amnesia and Alzheimer's disease (Hochhalter et al, 2000;López-Crespo et al, 2009;Martella et al, 2012;Plaza et al, 2011Plaza et al, , 2012. All these results can be explained according to the model suggested by Savage and colleagues (e.g., Overmier, Savage, & Sweeney, 1999;Ramirez, Buzzetti, & Savage, 2005;Savage, 2001;Savage & Parsons, 1997), who proposed that there are two different memory systems that are activated by differential and nondifferential outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, this is the first time that such an effect has been reported in 7-year-old children. Some recent studies have shown that the DOP is effective in improving memory-based performance after short delays in normal aging, in young people, and in patients with alcohol-related amnesia and Alzheimer's disease (Hochhalter et al, 2000;López-Crespo et al, 2009;Martella et al, 2012;Plaza et al, 2011Plaza et al, , 2012. All these results can be explained according to the model suggested by Savage and colleagues (e.g., Overmier, Savage, & Sweeney, 1999;Ramirez, Buzzetti, & Savage, 2005;Savage, 2001;Savage & Parsons, 1997), who proposed that there are two different memory systems that are activated by differential and nondifferential outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, they found that three patients with alcohol-induced amnesia showed significantly better delayed face recognition when differential outcomes were arranged. Later on, the potential of the DOP for aiding human memory has also been evident in four studies conducted with young people (Martella, Plaza, Estévez, & Fuentes, 2012;Plaza, Estévez, López-Crespo, & Fuentes, 2011), with older adults (López-Crespo, Plaza, Fuentes, & Estévez, 2009), and with Alzheimer's disease patients (Plaza, López-Crespo, Antúnez, Fuentes, & Estévez, 2012). In these studies, delayed face recognition performance of participants was improved by pairing each correct response with a specific outcome.…”
Section: Introductionmentioning
confidence: 94%
“…Participants were told that the prizes would be accumulated with correct responses and raffled off at the end of the experiment as a present for participation. Previous studies have demonstrated that raffling off the prizes at the end of the study is an effective way of promoting correct responses and therefore assessing the effects of the DOP (López-Crespo et al, 2009;Plaza et al, 2011). Fast responses were encouraged as participants were only allowed to press the response key within the aforementioned time frame.…”
Section: Methodsmentioning
confidence: 99%
“…The benefits of using the DOP also have been observed in people with discriminative learning difficulties, such as those with Down's syndrome (Estévez, Overmier, Fuentes, & González, 2003), adults with Prader-Willi syndrome (Joseph, Overmier, & Thompson, 1997), or children born prematurely (Martínez et al, 2012). Further studies have demonstrated that the DOP is effective at improving memory-based performance in healthy children (Martínez, Estévez, Fuentes, & Overmier, 2009;Martínez, Flores, González-Salinas, Fuentes, & Estévez, 2013), young adults (Martella, Plaza, Estevez, Castillo, & Fuentes, 2012;Plaza, Estévez, López-Crespo, & Fuentes, 2011), and older adults (López-Crespo, Plaza, Fuentes, & Estévez, 2009), as well as individuals with memory-based deficits, such as Korsakoff's syndrome (Hochhalter, Sweeney, Bakke, Holub, & Overmier, 2000) or Alzheimer's disease (Plaza, López-Crespo, Antúnez, Fuentes, & Estévez, 2012). It is of some interest to note that selfassociation has been shown to improve memory in patients with severe amnesia .…”
mentioning
confidence: 97%
“…A version of this found to be effective in both young adults (Miller et al, 2002) and elderly adults (Lopez-Crespo et al, 2009) is to follow each type of correct choice with an immediate unique outcome (e.g., photographs), whereby each delivery of this immediate outcome earns an entry into a lottery for unique prizes. Results of the lottery are announced at the end of training.…”
Section: A Summary Of Recommendationsmentioning
confidence: 99%